Pain management in a child with odontogenic orbital cellulitis and severe complications - Semkovych, Ya V; Semkovych, M Ya; Melnyk, T M; Gavrylyshyn , N I; Synoverska, O B (Pain medicine, 2022)
Introduction. Orbital cellulitis is a diffuse purulent inflammation of the orbital tissues followed by necrosis. Complications of orbital cellulitis include meningitis or cerebral vascular thrombosis leading to death. Background. We present the case of a 3-year-old child with orbital cellulitis and severe complications treated at the Departmentof Anesthesiology and Intensive Care, CNE “Ivano-Frankivsk Regional Children’s Clinical Hospital of Ivano-Frankivsk Regional Council”. Results. The child presented to the ophthalmology department with complaints of pronounced lid edema and hyperemia, right eye exophthalmos, massive purulent, foul-smelling discharge from the right eye, hyphema of the inner and outer corners of the eye, absent movements of the right eyeball, hyperthermia. Non-contrast computed tomography of the brain revealed osteomyelitis of the right maxilla, cellulitis of the right orbit, right-sided sinusitis, ethmoiditis. Under general anesthesia, there were performed deep orbitotomy, extraction of teeth 54, 55 with the extraction area drainage, puncture of the right maxillary sinus. Multimodal analgesia, detoxification therapy, empiric antimicrobial therapy, immune replacement therapy, protein replacement therapy, and syndromic treatment were chosen. On the 9th day, the child’s condition improved, and he was transferred to the ophthalmology department. On the 27th day of hospital stay, the child was discharged home in a satisfactory condition. Conclusions. The child’s recovery was achieved due to timely hospitalization and surgery, goal-directed antibiotic therapy, application of multimodal anesthesia principles and adequate pain management, immune replacement therapy, usage of non-specific detoxification methods and adequate rehydration therapy.